Implementation of shared decision-making about rooming-in: A before and after an audit of breastfeeding in Taiwan - Hsiao-Ying Hung; Chun-Che Wen; Pei-Fang Su; Shek-Yip Man; Ying-Ju Chang (BMC, 2024)
Abstract Background The 24-h rooming-in policy is crucial to the Baby-Friendly Hospital Initiative (BFHI) for promoting breastfeeding. However, this policy may restrict maternal autonomy. In 2018, to integrate women's preferences into care decisions, Taiwan's Baby-Friendly certification included prenatal shared decision-making (SDM) for rooming-in. Prior to 2018, maternal knowledge, considerations, and intentions regarding rooming-in and the impact of prenatal SDM were unknown. Methods A retrospective electronic medical record cohort study was conducted in southern Taiwan. Data on healthy postpartum women eligible for rooming-in and breastfeeding for the years 2017 and 2019, reflecting the periods before and after prenatal SDM was introduced, were gathered. Maternal and newborn characteristics, maternal knowledge, considerations, and prenatal intentions for postpartum rooming-in and breastfeeding during hospitalization were collected. Additionally, data on actual postpartum rooming-in practices during hospitalization and exclusive breastfeeding (EBF) practices from birth to hospital discharge, to 1 month, and to 2 months postpartum were collected. Descriptive and non-parametric statistics were applied to analyze the data. Results A total of 621 women in 2017 and 311 women in 2019 were included. After prenatal SDM was introduced, the rooming-in rate during hospitalization fell from 42.2% in 2017 to 25.6% in 2019 (p < 0.001), and the EBF rate declined from 45.9% to 35.7% (p = 0.01). Additionally, the 1-month postpartum EBF rate decreased from 46.4% in 2017 (n = 571) to 44.3% in 2019 (n = 264), and the 2-month postpartum EBF rate dropped from 45.5% in 2017 (n = 591) to 40.2% (n = 308). According to the 2019 Patient Decision Aids responses (n = 236), women demonstrated limited understanding of rooming-in, with only 40.7% expressing an intention toward 24-h rooming-in. Women of older maternal age (p < 0.001), with a graduate degree (p = 0.02), full-time employment (p = 0.04), and concerns about rest disruption (p < 0.001), were more likely to prefer non-24-h rooming-in. Conclusions Initiatives must promote prenatal SDM to enable healthcare providers to address misconceptions and tailor education, thereby increasing women's intention toward 24-h rooming-in and EBF. Future research should explore women's experiences and unmet needs at BFHI facilities to inform the construction of a baby- and mother-friendly environment.